Explaining the Strategic Model of Iran's Trade Diplomacy in World Expo Exhibitions - Rajabzadeh, Ali; Vazifehdost, Hosein; Zarezadeh, Fahimeh (Management Strategies and Engineering Sciences, 2024)
World Expo exhibitions, due to their unique structure, are among the important platforms for implementing governments’ trade diplomacy. The present study aims to explain the strategic model of Iran's trade diplomacy in World Expo exhibitions. The research is applied in terms of its purpose and is mixed-exploratory in terms of its paradigm. In the qualitative phase, interviews were conducted with 15 trade diplomats, businesspersons, university professors, and World Expo organizers until theoretical saturation was achieved. In the quantitative phase, based on Cochran's formula, 384 participants, including trade diplomats, businesspersons, university professors, and World Expo organizers, were selected through simple random sampling. In the qualitative section, thematic analysis was used to analyze the interviews. Accordingly, 33 concepts and 8 indicators were identified and classified based on coding and their relationship with the main dimensions. The proposed strategic model for Iran's trade diplomacy in World Expo exhibitions includes eight components: cultural representation, presentation of business and economic opportunities, trade negotiation, resource management, national branding, private sector participation, development of a trade diplomacy document (transparent articulation of the trade diplomacy document), and research and development. Subsequently, using exploratory factor analysis, the dimensions forming Iran's trade diplomacy in World Expo exhibitions were identified, and the validity of the proposed model was confirmed through confirmatory factor analysis using Amos software.